A right pulmonary vein abnormality treated with 3D CT assistance in thoracoscopic surgery for esophageal cancer: a case report - Naoki Kuwayama; Isamu Hoshino; Hisashi Gunji; Toru Tonooka; Hiroaki Soda; Takeshi Kurosaki; Nobuhiro Takiguchi; Yoshihiro Nabeya; Wataru Takayama (Surgical Case Reports, 2022)
Abstract Background Anomalous bifurcation of the right superior pulmonary vein is an important anomaly that should be recognized not only in respiratory and cardiac surgeries, but also in esophageal surgery for the safe performance of surgery. We report a case in which thoracoscopic esophagectomy was safely performed using preoperative three-dimensional computed tomography (3D CT) imaging. Case presentation An 81-year-old male patient received an upper gastrointestinal endoscopy, which revealed a 20-cm incisor at the entrance, 43-cm EGJ, and 30-mm large type 1 + IIc lesion between the 23-cm and 26-cm incisors; biopsy showed squamous cell carcinoma (SCC). Contrast-enhanced CT showed wall thickening in the anterior wall of the upper thoracic esophagus, without evidence of multi-organ invasion or lymph node metastasis. In addition, a break in the right pulmonary vein passing dorsal to the right main bronchus and flowing directly into the left atrium was observed, and 3D CT was performed preoperatively to confirm the 3D positioning. Positron emission tomography (PET)–CT showed a high degree of accumulation (SUVmax 19.95) in the upper thoracic esophagus. The patient was diagnosed with upper thoracic esophageal cancer, cT2N0M0 cStage II, and underwent thoracoscopic subtotal esophagectomy (three-region dissection) and gastric tube reconstruction. The dorsal inflow of the pulmonary vein in the right main bronchus, which was recognized on preoperative CT, was confirmed and preserved. The pathological diagnosis was basaloid squamous cell carcinoma, pT1b(SM1)N0(0/58)M0 pStage I. The postoperative course was uneventful, and the patient was discharged on postoperative day 20. Conclusions The anomalous bifurcation of the pulmonary vein in the right upper lobe area required attention because of its potential to cause massive bleeding and difficulty in securing the operative field if misidentified and damaged during surgery. Although it is not frequently encountered, it is the bifurcation anomaly that esophageal surgeons must bear in mind due to its severe consequences. Preoperative image-reading and intraoperative manipulation of this vessel are imperative for surgical safety.